2020
DOI: 10.3390/w12123410
|View full text |Cite
|
Sign up to set email alerts
|

Experience from the Implementation and Operation of the Biological Membrane Reactor (MBR) at the Modernized Wastewater Treatment Plant in Wydminy

Abstract: Biological membrane reactors or membrane bioreactors (MBRs) based on pressure separation techniques are placed among the latest and most modern methods of wastewater treatment. Currently, this method is becoming more and more popular and is being implemented in smaller and larger wastewater treatment plants (WWTPs). However, technologists, operators, and managers of small WWTPs often do not understand the MBR technology installed in their sites and need extensive professional and technological information. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…The first facility, the wastewater treatment plant in Kunow, uses the technology of biological membrane reactors. MBR technology is recognized as the best possible technology for wastewater treatment (BAT = best available technology) within the meaning of the IPPC Directive, Integrated Pollution Prevention and Control [ 36 , 37 ]. Ultrafiltration on membranes allows maintaining in the biological reactor a many times higher concentration of activated sludge (8–12 g/m 3 ) than is allowed for secondary settling tanks.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The first facility, the wastewater treatment plant in Kunow, uses the technology of biological membrane reactors. MBR technology is recognized as the best possible technology for wastewater treatment (BAT = best available technology) within the meaning of the IPPC Directive, Integrated Pollution Prevention and Control [ 36 , 37 ]. Ultrafiltration on membranes allows maintaining in the biological reactor a many times higher concentration of activated sludge (8–12 g/m 3 ) than is allowed for secondary settling tanks.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…It has been shown that pharmaceuticals can be removed only partially, as these wastewater treatment plants are not designed for full removal [1]. Depending on the composition of wastewaters, preliminary treatments with activated sludge systems or classic membrane bioreactors may be needed [45]. However, membrane fouling comprises a significant obstacle to their broad application [46].…”
Section: Conventional Treatmentsmentioning
confidence: 99%
“…Since the DEGBR operates anaerobically, it has two significant drawbacks, (i) it is ineffective in removing nitrates and phosphorous, and (ii) it reduces the organic nitrogen and sulphur to ammonia and hydrogen sulphide, which are toxic, hence the need for incorporating a membrane bioreactor stage as post-treatment. The advantages of MBR compared with a conventional activated sludge process include high effluent quality, decreased reactor volume, elevated solid retention time (SRT) and high mixed liquor suspended solids (MLSS), low sludge yield, and easier operation [58,59]. However there are still some drawbacks associated with MBRs such as; membrane fouling, high energy consumption and low removal efficiency of poorly biodegradable micropollutants like diclofenac, atrazine, and carbamazepine [58].…”
Section: Hybrid Membrane Bioreactormentioning
confidence: 99%
“…A comparison study was done by Skoczko, Puzowski [59] to compare the modernized vs conventional treatment methods on a newly modernized wastewater treatment plant. On the basis of the conducted research, it was noted that the operation of the plant after modernization was more cost-intensive.…”
Section: Applications Of Membranes In Wastewater Treatmentmentioning
confidence: 99%